Comparison between nab-paclitaxel and solvent-based taxanes as neoadjuvant therapy in breast cancer: a systematic review and meta-analysis - Liu, Miao (BMC Cancer, 2021)
BACKGROUND: To compare the efficacy and safety of nanoparticle albumin-bound paclitaxel (nab-paclitaxel) and solvent-based taxanes (sb-taxanes) as neoadjuvant therapy in the treatment of breast cancer. METHODS: We systematically searched the PubMed, Embase, and Cochrane Central Register databases. Randomized controlled trials (RCTs) and cohort studies, published in English, about the comparison between nab-paclitaxel and sb-taxanes as neoadjuvant therapy in patients with breast cancer were searched up to September 2019. RESULTS: The primary outcome was the proportion of patients with pathological complete response (pCR, defined as ypT0 ypN0 or ypT0/is ypN0). Other main outcomes included long-term survival and adverse events (AEs). Seven studies (five RCTs and two cohorts) and 2949 patients were included. Neoadjuvant nab-paclitaxel improved pCR compared with sb-taxanes (ypT0 ypN0: OR = 1.52, 95%CI: 1.27–1.83, P < 0.001; ypT0/is ypN0: OR = 1.40, 95%CI: 1.17–1.68, P < 0.001). The benefits of nab-paclitaxel on pCR were persistent in HER2-negative, hormone receptor (HR)-positive breast cancer (OR = 1.53, 95%CI: 1.07–2.19, P = 0.020), triple-negative breast cancer (weekly/every 2 weeks regimen; OR = 2.95, 95%CI: 1.54–5.67, P < 0.001), and tumors with Ki-67 > 20% (OR = 1.63, 95%CI: 1.26–2.12, P < 0.001). Patients treated with nab-paclitaxel had better event-free survival (EFS; HR = 0.69, 95%CI: 0.57–0.85, P < 0.001) than with sb-taxanes. There were no differences in most of grade > 3 AEs between nab-paclitaxel and sb-taxanes (all P > 0.05), besides of any grade hypersensitivity (OR = 0.29, 95%CI: 0.11–0.72, P = 0.008), any grade (OR = 2.10, 95%CI: 1.37–3.23, P = 0.001) and grade > 3 (OR = 4.01, 95%CI: 2.51–6.41, P < 0.001) neuropathy. CONCLUSION: Nab-paclitaxel is effective for the treatment of non-metastatic breast cancer in the neoadjuvant setting. Nab-paclitaxel could improve pCR rate and EFS compared with sb-taxanes and with reasonable toxicities. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12885-021-07831-7.